2010
DOI: 10.1097/jto.0b013e3181f38816
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Age at Diagnosis and the Presence of EGFR Mutations in Female Patients with Resected Non-small Cell Lung Cancer

Abstract: Background: Our previous report showed an association between age and outcome in gefitinib-treated female patients with non-small cell lung cancer (NSCLC). Only limited numbers of molecular studies have been performed with respect to the presence of epidermal growth factor receptor (EGFR) mutations according to age. This retrospective study was performed to evaluate a possible association between age at the time diagnosis and the presence of EGFR mutations in female patients with NSCLC. Methods: Tumor specimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
17
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 36 publications
9
17
1
Order By: Relevance
“…EGFR mutations are common in older, female, non-smoking patients with well-differentiated tumors (especially bronchioloalveolar carcinoma) [12,17,18]. Our study’s findings are in accordance with these reports in the Han group: EGFR mutation associated with sex, smoking history, and the degree of tumor differentiation.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…EGFR mutations are common in older, female, non-smoking patients with well-differentiated tumors (especially bronchioloalveolar carcinoma) [12,17,18]. Our study’s findings are in accordance with these reports in the Han group: EGFR mutation associated with sex, smoking history, and the degree of tumor differentiation.…”
Section: Resultssupporting
confidence: 91%
“…Research shows that tumor response to erlotinib is greater in patients with exon 19 mutation compared with patients with exon 21 mutation [18]. In our study, the Uighur group’s mutation rate in exon 19 was higher than that in exon 21 (66.7% vs 33.3%), which is similar to Caucasian population [18].…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…[17,19] Although statistical difference could not be reached with a limited sample size of non-adenocarcinoma and smokers, it appears that a relationship between smoking history and mutational status is not prominent in Asian female patients, [17,31,32] indicating their unique characteristics compared with Western patients.…”
Section: Discussionmentioning
confidence: 99%
“…[10,11] In particular, molecular data have shown that female patients are associated with a high incidence of epidermal growth factor receptor (EGFR) mutation. [12] According to Eastern studies, [13][14][15][16][17] Asian female NSCLC patients are predominantly never-smokers and are likely to have adenocarcinoma histology. Molecular studies have also reported that Eastern ethnicity is associated with a high incidence of EGFR mutation, [18] a factor that strongly predicts outcomes after treatment with tyrosine kinase inhibitors (TKIs) such as gefitinib or erlotinib.…”
Section: Introductionmentioning
confidence: 99%